(untitled) (GAIMS Journal of Medical Sciences, 2022)
Alopecia areata (AA) is a non-cicatricial alopecia that is postulated to be a hair-specific autoimmune disease, with genetic factors playing a role in disease susceptibility and severity. The most common form of disease manifests as smooth, discrete, round patches of hair loss and can be referred to as alopecia areata focalis (AF). Tofacitinib is emerging as a promising therapy for severe AA. An increasing number of studies have demonstrated the efficacy of tofacitinib in treatment of alopecia areata. Herein we report a case of recalcitrant alopecia areata in a 14-year-old female treated successfully with oral tofacitinib based therapy.